PENGARUH KEGIATAN USAP ABUR TIGA DIMENSI TERHADAP KEMAMPUAN MENGGAMBAR ANAK DI TAMAN KANAK-KANAK KEMALA BHAYANGKARI 1 PADANG - Jasmine Yaasin; Farida Mayar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The lack of development of drawing skills in early childhood is the background for conducting research. This happens because drawing activities use monotonous techniques which cause children to be less enthusiastic during drawing activities which will have an impact on the lack of development of the child's level of drawing ability. The aim of this research is to find out how much influence three-dimensional wiping activities have on children's drawing abilities at Kemala Bhayangkari 1 Kindergarten Padang. The type of research used quantitative research in form of a quasi-experiment. The research was conducted at Kemala Bhayangkari 1 Padang Kindergarten, 12 children in groups B2 and B3 as the experimental class and the control class were used as samples. The next stage of data collection is implementation of action tests and documentation. Then, data analysis is used normality tests, homogeneity tests, and hypotheses. Based on the results of t-test calculations using the SPSS 25 application, a Sig (2-tailed) value of 0.024 was obtained, where this value was smaller than the value of 0.05 (0.24<0.05). So Ho is rejected and Ha is accepted. Based on the data, it can be concluded that the three-dimensional smear activity has an effect on the drawing ability of young children.